The relationship between spirituality and leader’s effectiveness: a perspective from the Holy Qur’an - Zandi Pour Joopari, GholamReza; Sulaiman, Mohamed; Naysary, Babak; Rashed, Nayal (Caspian Journal of Applied Sciences Research, 2013)
This research is an attempt to reveal leadership concepts from the Qur'an. Despite decades of ongoing inquiry and increasing interest, research on leadership has ignored religious elements, especially form the Qur'an as a source of knowledge. Based on the characteristics of the Motaqeen according to the Qur'an, the concept of Taqwa has been operationalized as having two distinct components, that is, Spirituality and Responsibility. This study tries to examine the relationship between the first component i.e. spirituality and leader's effectiveness. A cross-sectional field study was carried out in which spirituality was a self-constructed measurement while leadership effectiveness was constructed from existing scales in the literature. Multiple regression and hierarchal regression techniques using SPSS were used to test the hypotheses utilizing sample of 206 companies. The results show that leaders' level of spirituality influences the leaders' effectiveness, where one dimension of Spirituality, that is Belief, was found to predicate business leadership effectiveness. In the light of findings of present research several recommendations are made to improve the Spirituality of leaders within the organizational culture.